Molecular orientation and electrical properties of 4-cyano-4′-n-heptylbiphenyl-salicylaldimine compound composite liquid crystals by dielectric impedance spectroscopy and current-voltage techniques - Canli, N. Yilmaz; Yakuphanoglu, F.; Bilgin-Eran, B. (NATL INST OPTOELECTRONICS, 2009)
The dielectric and current voltage properties of 4-cyano-4'-n-heptylbiphenyl doped LC1 and LC2 salicylaldimine compounds have been investigated. The polarizing microscopy and differential scanning calorimetry results show that the salicylaldimine compounds (LC1, LC2) exhibit liquid crystalline properties. The salicylaldimine compound LC1 exhibits SmC and SmA mesophases, while LC2 exhibits only SmA mesophase. The dielectric anisotropy of the LCs was found to vary from positive type to negative type. The LC1 liquid crystal significantly the dielectrical anisotropy behavior of the 7CB. The dielectrical relaxation mechanism analyzed by the Cole-Cole plots of the liquid crystals is close to Debye type relaxation behavior. The current voltage characteristics indicate that the 7CB and 7CB/LC1 liquid crystals exhibit voltage-controlled differential negative resistance (VCNR) behavior. It is evaluated that the molecular orientation and electrical properties of the 7CB liquid crystal can be controlled by salicylaldimine compounds.
Keywords: Liquid crystal; Dielectric anisotropy; Salicylaldimine; DIPOLE-MOMENT; ANISOTROPY; Materials Science; Optics